Design, simulation and experimental characterization of a high-power density fuel cell. (26th July 2021) - Pacheco, C.; Barbosa, R.; Ordoñez, L.C.; Sierra, J.; Escobar, B.
Abstract: This research proposes a novel design of a millimeter-sized air-breathing proton exchange membrane fuel cell (AB-PEMFC). The producing method of the air-breathing PEMFC consisted of the sequential deposition of the elements in layers: 1) endplate of a flat polymer, 2) fuel flow channel with gas diffusion layers (GDL), 3) silicone seal with embedded micro Pt (platinum) wires, 4) membrane electrode assembly (MEA) with high platinum load, 5) GDL with micro Pt wires. Performance tests were done using an AB-PEMFC and the stack of two mono cells under different conditions. The results obtained by the computational fluid dynamics (CFD) allowed analyzing the current collector (CC) position. The performance results show 110 W L −1 for the cell power density and 2200 W kg −1 for the specific power density. Highlights: A new design by air-breathing mili-PEMFC is presented. The mili-PEMFC was characterized using experimental and CFD techniques. CFD simulation of the mili-PEMFC under different conditions. The results were validated using polarization curves and experimental data.